Metabotropic Glutamate Receptor 8 Is Regulated by miR-33a-5p and Functions as an Oncogene in Breast Cancer. (14th December 2021) - Zhang, Chunxu; Xie, Shuang; Yuan, Shouxin; Zhang, Yuanhao; Bai, Yunhu; Chu, Lijia; Wu, Zuyin; Guo, Ninghui; Wang, Quanhui; Zhang, Jixin
Abstract : It has been reported that glutamate metabotropic receptor 8 (GRM8) is closely implicated in the progression of human neuroblastoma, lung cancer, and glioma, but its role in breast cancer remains unknown. Thus, the present study was performed to uncover it. Immunohistochemistry, real-time PCR (RT-PCR), and western blotting experiments were performed to test GRM8 expression levels in tissues and cells. Cell functions were assessed by Cell Count Kit 8 (CCK-8), flow cytometry, wound healing, transwell chambers, and in vivo xenotransplantation experiments. The relationship between miR-33a-5p and GRM8 was evaluated by luciferase gene reporter and western blotting assay. The results showed that GRM8 expression was increased in breast cancer tissues and cells, which was closely associated with lower overall survival rate. Ectopic expression of GRM8 significantly enhanced cell growth, migration, and invasion and tumorigenesis and repressed cell apoptosis. In addition, GRM8 was under the negative regulation of miR-33a-5p, which was downregulated in breast cancer tissues and served as a tumor suppressor. Moreover, overexpression of GRM8 abrogated the inhibitive role of miR-33a-5p played in breast cancer. Collectively, this study reveals that GRM8 functions as an oncogene in breast cancer and is regulated by miR-33a-5p.